2004
DOI: 10.1021/ja0377605
|View full text |Cite
|
Sign up to set email alerts
|

Optical and Electrical Properties of Three-Dimensional Interlinked Gold Nanoparticle Assemblies

Abstract: The optical and electrical properties of 11-20 nm thick films composed of approximately 4 nm gold nanoparticles (Au-NPs) interlinked by six organic dithiol or bis-dithiocarbamate derivatives were compared to investigate how these properties depend on the core of the linker molecule (benzene or cyclohexane) and its metal-binding substituents (thiol or dithiocarbamate). Films prepared with the thiol-terminated linker molecules, (1,4-bis(mercaptomethyl)benzene, 1,4-bis(mercaptomethyl)cyclohexane, 1,4-bis(mercapto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
230
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 237 publications
(240 citation statements)
references
References 37 publications
(94 reference statements)
8
230
1
1
Order By: Relevance
“…Of greatest interest is the potential to precisely tune both the optical and electronic properties of the films by controlling both the individual particle size and the interparticle spacing, the latter now with molecular-scale precision through the choice of appropriate protecting or capping molecules surrounding the gold particle. [49,50] In a recent timely contribution Pelka et al reported extensive studies on selfassembled thin films of gold nanoparticles of 4-5 nm diameter, prepared on glass, using aliphatic dithiols of different hydrocarbon chain lengths as interparticle linker molecules. [51] Importantly, the dc conductivity of these films (s), measured down to 4.2 K, shows a strong dependence on the intervening spacer length, effectively traversing the different mechanisms of electrical conductivity through the films: from thermally activated electron hopping between gold particles in films with longer-chain linker molecules, changing to electron tunnelling at low temperatures, ultimately to become metallic when the interparticle linker is shorter (Figure 9).…”
Section: Methodsmentioning
confidence: 99%
“…Of greatest interest is the potential to precisely tune both the optical and electronic properties of the films by controlling both the individual particle size and the interparticle spacing, the latter now with molecular-scale precision through the choice of appropriate protecting or capping molecules surrounding the gold particle. [49,50] In a recent timely contribution Pelka et al reported extensive studies on selfassembled thin films of gold nanoparticles of 4-5 nm diameter, prepared on glass, using aliphatic dithiols of different hydrocarbon chain lengths as interparticle linker molecules. [51] Importantly, the dc conductivity of these films (s), measured down to 4.2 K, shows a strong dependence on the intervening spacer length, effectively traversing the different mechanisms of electrical conductivity through the films: from thermally activated electron hopping between gold particles in films with longer-chain linker molecules, changing to electron tunnelling at low temperatures, ultimately to become metallic when the interparticle linker is shorter (Figure 9).…”
Section: Methodsmentioning
confidence: 99%
“…Some experiments demonstrate the possibility of control coupling strength by means other than controlling the length the molecule, such as NP coverage and film thickness. [13,14] Though successfully explaining the observed transition, the above picture is based on the regularity of the NP assembly, in which the randomness cannot simply be neglected. There are at least three types of randomness: NP position and size, interparticle coupling, and random offset charges.…”
Section: Introductionmentioning
confidence: 99%
“…The latter results suggest that the molecular orbitals of the linking molecules play an important role in the electron transport properties of the gold nanoparticle assemblies. Wessels et al 6 have studied the conductivity of gold nanoparticle assemblies from the viewpoint of the conjugation strength of the molecules. They found that the conductivity exhibited an exponential decay versus the number of nonconjugated bonds in the linker molecule, suggesting that these molecules can be viewed as being serial connections of electrically insulating ͑nonconju-gated͒ and conductive ͑conjugated͒ parts.…”
Section: Introductionmentioning
confidence: 99%